THE EFFECT OF HUMAN RESOURCES ACCOUNTING ON THE SPECIFIC COSTS OF OIL PRODUCTS: AN APPLIED STUDY IN SOUTH REFINERIES COMPANY - Sadiq Jafar Kathim; Nadhim Khasran Hassooni Al Shaibani; Samaher Sadeq Ali AL- Gburi (Journal Park Publishing, 2024)
In order to produce high-quality products with competitive specifications, human resources training programs must be developed and paid attention to very significantly through two executors, either selling these products at prices higher than the prices of competing products in the market or reducing costs related to production, and this ultimately leads to an increase in profits per unit, hence the need to pay attention and recognize the great role played by human resources in all economic aspects and take into account accounting for human resources. From this side, the current research dealt with human resources accounting and its impact on qualitative costs, has been determining the specific costs in the South Refineries Company for Petroleum Products and then a statement of the reality of training and development in the company has reached the research a set of conclusions, the most important of which is that 70% of the economic units do not have full know-how and access to the concept of qualitative costs and their constituent elements and thus the role of human resources accounting in benefiting from trained human resources to perform work with the highest levels of efficiency and speed possible and qualitative The most important recommendations of the research are the need to support studies, research and conferences related to human resources accounting and qualitative costs and the need to develop appropriate training programs for different specializations and follow up their implementation and evaluation, which achieves optimal investment of the costs related to them.